Fabrication of lightweight polymer products with excellent mechanical properties using a novel double-sided in-mold decoration combined with fiber-reinforced microcellular injection molding process - Shengrui Yu; Kai Wang; Lei Xu; Senzhen Song; Jiangen Yang; Wen Han; Huamin Zhou (Journal of Materials Research and Technology, 2024)
This paper introduces a novel molding process known as the double-sided in-mold decoration combined with fiber-reinforced microcellular injection molding (DS-IMD/FR-MIM) process. This process utilizes supercritical fluids to grow a microcellular structure for a lightweight product and adds glass fibers into polymer particles to reinforce mechanical properties. Concurrently, double-sided in-mold decoration (DS-IMD) technique provides a symmetric temperature field for melts during filling stage and high surface quality for parts after cooling. Tensile splines are simulated and tested to examine the impacts of various in-mold decoration methods on the melt temperature, freezing layer fraction, fiber orientation, cellular morphology and distribution, and mechanical properties. Applied splines include undecorated and fiber-reinforced microcellular injection molding (FR-MIM) spline, single-sided in-mold decoration combined with fiber-reinforced microcellular injection molding (SS-IMD/FR-MIM) spline, and DS-IMD/FR-MIM spline. Additionally, a flexural spline is used to test its flexural strength and surface quality. The results show that DS-IMD/FR-MIM process provides slower freezing speed and better foaming effect than FR-MIM process. It also generates more symmetric cellular distribution and more orderly fiber distribution than SS-IMD/FR-MIM process. DS-IMD/FR-MIM splines have high surface quality on decorated surfaces and 10.2 % weight loss. By comparison with FR-MIM and SS-IMD/FR-MIM splines, DS-IMD/FR-MIM splines increase an elongation at break by 24.3 % and 14.8 %, respectively. This paper contributes a feasible approach and theoretical groundwork for the fabrication of lightweight products with excellent mechanical strength and appearance.